Study the effect of aqueous extract of Yas Rue on the types of bacteria isolated from wounds and burns (Baghdad Science Journal, 2005)
The current study was conducted to determine the sensitivity of some pathogenic bacterial isolates isolated from wounds and burns water toward the disposer of the Yas Rue tested five crude bacterial isolates isolated from wounds and burns which these isolates sensitive to aqueous extract crude